Shred sisters : a novel - Lerner, Betsy (Grove Press, an imprint of Grove Atlantic, 2024)
"From Betsy Lerner, celebrated author of The Bridge Ladies, comes a wry and riveting debut novel about family, mental illness, and a hard-won path between two sisters. It is said that when one person in a family is unstable, the whole family is destabilized. Meet the Shreds. Olivia is the sister in the spotlight, but when her stunning confidence morphs into something erratic and unpredictable, she becomes a hurricane leaving the Shred family wrecked in her wake. Put simply, she has no brakes. Younger sister Amy, cautious and studious to the core, dreams of winning a Nobel Prize in science. Amy believes in facts, proof, and the empirical world. Except none of that can explain what's happening to Ollie, whose physical beauty and charisma mask the bipolar disorder that will shatter Amy's carefully constructed world. As Amy comes of age and seeks to find her place-first in academics, then New York publishing, and through a series of men-every step brings collisions with Ollie. For all that upends and unsettles these sisters, an inextricable bond always draws them back. Spanning two decades, Shred Sisters is an intimate and bittersweet story exploring the fierce complexities of sisterhood, mental health, loss and love. If anything is true it's what Amy learns on her road to self-acceptance: No one will love you or hurt you more than a sister"--